Covalent organic framework photocatalysts for green and efficient photochemical transformations - Yongzhi Chen; Yuanyuan Guo; Tie Wang; Sailun Ji; Haipei Shao; Ming Lin; Shu Seki; Ning Yan; Donglin Jiang (Nature Communications)
Abstract Artificial photosynthesis is impeded by rapid charge recombination and inefficient use of photogenerated carriers. Here we present covalent organic frameworks with systematically tailored skeletons and pores for green yet efficient photosynthesis with water and air. The hexavalent frameworks with non-conjugated photocatalytic skeletons enable water oxidation at knot corners and oxygen reduction at linker edges, while orientated triangular micropores timely supply water and air. Noteworthily, the framework with the highest π density and smallest supermicropores exhibits optimal charge separation and utilization and achieves rapid, efficient and cyclable hydrogen peroxide production in both batch and membrane reactors. Remarkably, the supermicroporous framework instantly removes organic dye contaminants from water and fully degrades these dyes under visible light. Our findings enable a paradigm shift to the systematic design of both electron/hole flow and mass transport for constructing photocatalysts, which are not only scientifically important but also technologically key to shaping sustainable society and future.